The Legacy of Ferguson: Building Worker, Community, and Student Power To Respond to the Carceral State - Donna Coker; Melody Sinckler; Kira Mikes (Washington University Journal of Law and Policy, 2025)
The 2014 killing of Michael Brown in Ferguson, Missouri sparked national outrage regarding police violence in Black communities. But as time passed, Ferguson came to symbolize more than another episode of law enforcement violence. A Department of Justice (DOJ) report revealed that Ferguson’s city coffers relied on an intentionally extractive criminal legal system that aggressively levied fines and fees in a racially discriminatory manner. As the DOJ findings illustrate, advocates seeking to transform or abolish the criminal legal system must rigorously analyze the political economy of the carceral system in their locale. We describe a law school course aimed at this kind of analysis and action. The course, Building Worker and Community Power to Confront the Carceral State, was a collaboration between a law school class and a community organization, Beyond the Bars (BTB). BTB is a Miami-Dade County, Florida worker center that empowers people with criminal records, helps them reintegrate into society and family life, and organizes for policy changes that improve their economic position. The course engaged students in movement lawyering focused on the problems of mass incarceration and the economic exploitation of carceral system-impacted workers. Carceral practices create and deepen poverty and depress wages in labor sectors characterized by precarity and dangerous working conditions. By collaborating with BTB members on reforms to county policies, students developed an understanding of the systemic forces that sustain the criminal legal system, the experiences of those directly impacted by carceral policies, and the leadership capabilities of carceral system-impacted people. We conclude by describing the possibilities for legal education to support social movements committed to dismantling the carceral state.
Keywords: AbolishCarceralEconomy; MovementLawyering; FromFergusonToFreedom